2014
DOI: 10.17219/acem/30817
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase-Type Plasminogen Activator Receptor and Ferritin Concentration in Patients with Advanced Alimentary Tract Carcinoma. Relationship to Localization, Surgical Treatment and the Stage of the Disease – Preliminary Report

Abstract: Background. The urokinase plasminogen activation system is associated with metastatic potential of cancer in several tumors. Its specific membrane receptor (uPAR) is released from cancer cells and can be detected as the soluble fraction of the plasminogen activator receptor (suPAR). Ferritin (FRT) is a poor prognostic factor in various neoplasms. Objectives. We analyzed the serum concentrations of suPAR and FRT in patients with gastrointestinal cancer. Tumor localization, stage of the disease, possibility of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…suPAR is the soluble form of uPAR which, in cancer, is expressed on cancer cells and stromal cells . Several studies show an association between suPAR and the presence and prognosis of different types of cancer as well as an increased risk of developing lung cancer in the general population …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…suPAR is the soluble form of uPAR which, in cancer, is expressed on cancer cells and stromal cells . Several studies show an association between suPAR and the presence and prognosis of different types of cancer as well as an increased risk of developing lung cancer in the general population …”
mentioning
confidence: 99%
“…suPAR is the soluble form of uPAR which, in cancer, is expressed on cancer cells and stromal cells. [18][19][20] Several studies show an association between suPAR and the presence and prognosis of different types of cancer [21][22][23][24][25][26][27] as well as an increased risk of developing lung cancer in the general population. 28 Little is known as to how these biomarkers perform in a heterogeneous group of patients with diffuse and nonspecific symptoms.…”
mentioning
confidence: 99%
“…Serum ferritin levels became normal as tumors entered remission. Cancer patients with metastasis had higher serum ferritin than patients without metastasis and had lower serum ferritin after surgery 24. Nevertheless, the level of colon tissue ferritin was not related to the systemic parameters of iron metabolism 25.…”
Section: Discussionmentioning
confidence: 95%
“…No study had reported that Fer is an independent risk factor for the survival of ICC patients. However, plasma Fer concentrations were reported to be closely related to the occurrence and development of HCC, breast cancer, and gastrointestinal tumors 7-9 . Additionally, some researchers posited that in male patients, excessively high or low preoperative Fer concentrations are an independent risk factor for hepatitis C in HCC 7 .…”
Section: Discussionmentioning
confidence: 99%